ANALISIS PENGARUH KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN PADA PT.PELNI (PERSERO) CABANG PAREPARE - Sukma, Sukma (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of environmental performance on firm value. The data collection technique used is a questionnaire. The results showed that the firm value variable had a significance of 0.030. The significance value of 0.030 is smaller than the significance value of α, namely 0.05. that shows that the environmental performance variable influences firm value.